Digital Literacy and Children's Social Behavior: The Role of Parental Interaction Quality in Parenting in the Gadget Era - Azizah, Umi Fajar; Rosita, Kusnulia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The extensive proliferation of digital technology among elementary school-aged children frequently poses the risk of social behavioral issues and diminished empathy, attributed to insufficient self-regulation and inadequate supervision. This study seeks to investigate the intricate mechanisms underlying the relationship between children's digital literacy and their social behavior by analyzing the dual function of parental interaction quality (Parenting Style) as both a mediator and a moderator.  Data were gathered from 105 elementary school students in Surakarta City utilizing a quantitative correlational methodology.  The hypothesis testing yielded significant results:  The study demonstrated that parenting style serves as a mediator, indicating that the beneficial effects of digital literacy on social behavior primarily manifest through the perception of positive parenting.  Additionally, Parenting Style served as a moderator, validating that the beneficial effects of digital literacy are amplified when the quality of parental engagement is elevated.  These results highlight the need to improve Digital Parenting programs that stress the importance of open communication and active parental involvement as key elements in making sure that children's digital skills lead to good behavior.